Description of students' science process skills on density material - Tanti Tanti; Dwi Agus Kurniawan; Aziza Putri Ningsi (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2020)
Physics is one of the subjects related to various scientific concepts in which some of its applications can be found in everyday life. Thus in the learning of physics required special skills, namely science process skills. Science process skills have two categories, basic science process skills, and integration science processes. The researcher conducted research that aims to measure the ability of students' science process skills on static fluid material by using an observation sheet that matches the indicators of science process skills. The research method used is a mixed-method (mix methods) while the design used is sequential explanatory, which combines quantitative and qualitative research in a sequence using the quantitative method and then the quantitative method. From the results of interviews and observations, it can be seen that the science process skills of students at Adhyaksa 1 Junior High School in Jambi are classified as good.